ANALISIS PENGARUH KECEPATAN BELT CONVEYOR JALUR 7.1 TERHADAP PRODUKTIVITAS LIMESTONE KE STORAGE PABRIK INDARUNG VI DI PT SEMEN PADANG. - Muhammad Fajar Rahman; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2023)
In terms of delivering limestone to the plant, the process of delivering material using a belt conveyor and crushing using a Lime Stone Crusher (LSC). Belt widths range from 1 meter to 1.2 meters, 1.4 meters to 1.8 meters. How each belt varies in speed, each gearbox installed by the belt conveyor motor has varying capabilities.The author uses a descriptive research design. The descriptive method is a technique that offers many options for solving problems through the collection, compilation, or classification of data, analysis, and interpretation of the data. Therefore, it is necessary to increase production by increasing the efficiency of the belt conveyor conveyance. Recommendations for increasing the productivity of the 6A1J06 conveyor belt with a speed of 3 m / s, an idler angle of 30 ° and a belt width of 1600 mm with a result of 2169.09 tons / hour and for the 6A1J10 conveyor belt with a speed of 2 m / s, an idler angle of 30 ° and a belt width of 1800 mm with a result of 2079.09 tons / hour. Simulation of improvements made by eliminating or reducing obstacles that occur in the performance of the conveyor belt or other factors outside the performance of the conveyor belt is able to meet the production targets of the company, where the effective working time from 389.20 hours / month to 531.42 hours / month. This will certainly increase the work efficiency value of the conveyor belt conveyance, which initially 57.91% increased to 79.08% with an increase in limestone production of 1,089,607 tons (126%).